Exploitation of host clock gene machinery by hepatitis viruses B and C - Vinciguerra, Manlio (Baishideng Publishing Group Co., Limited, 2013)
Many aspects of cellular physiology display circadian (approximately 24-h) rhythms. Dysfunction of the circadian clock molecular circuitry is associated with human health derangements, including neurodegeneration, increased risk of cancer, cardiovascular diseases and the metabolic syndrome. Viruses triggering hepatitis depend tightly on the host cell synthesis machinery for their own replication, survival and spreading. Recent evidences support a link between the circadian clock circuitry and viruses’ biological cycle within host cells. Currently, in vitro models for chronobiological studies of cells infected with viruses need to be implemented. The establishment of such in vitro models would be helpful to better understand the link between the clock gene machinery and viral replication/viral persistence in order to develop specifically targeted therapeutic regimens. Here we review the recent literature dealing with the interplay between hepatitis B and C viruses and clock genes.